2007
DOI: 10.1109/tsm.2007.901826
|View full text |Cite
|
Sign up to set email alerts
|

Voltage Contrast for Gate-Leak Failures Detected by Electron Beam Inspection

Abstract: We examine a technique for enhancing the voltage contrast (VC) of a failure analysis (FA) tool, defect review scanning electron microscope (DR-SEM). For an SRAM, we demonstrate a dependence of gate-leak VC on the relative angle (RA) between the direction of beam scanning by the FA tool and the lengthwise direction of the gate electrode. Experimental results show that better VC results are obtained when RA is zero, in other words, a beam's scan-line is parallel with the SRAM gate. We propose a simple qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The junction leakage current failure over 1 times 10 to the power of 5 pA/μm occurs in some transistors randomly. For the first step of failure analysis, to localized fault transistor, voltage contrast (VC) inspection by using scanning electron microscopy (SEM) was performed [17]. And then, in order to reveal the failure cause, we performed failure analysis using advanced TEM techniques.…”
Section: B Spatially-resolved Eelsmentioning
confidence: 99%
“…The junction leakage current failure over 1 times 10 to the power of 5 pA/μm occurs in some transistors randomly. For the first step of failure analysis, to localized fault transistor, voltage contrast (VC) inspection by using scanning electron microscopy (SEM) was performed [17]. And then, in order to reveal the failure cause, we performed failure analysis using advanced TEM techniques.…”
Section: B Spatially-resolved Eelsmentioning
confidence: 99%
“…VC-based inspection is already established for local contact, gate-leak, and dynamic random access memory capacitor. [4][5][6][7] Failure mode classification was demonstrated by changing the scan direction of EB, considering the device circuit. 8 The VC method should be applicable to NW-SD contact inspection, although there is no experimental verification yet.…”
Section: Introductionmentioning
confidence: 99%
“…Qualitatively, the impact of changing the scan direction of EB was discussed with an RC model. 7,8 It is already reported that rough estimation of parasitic resistance is only possible by evaluating VC. 10 Pulsed irradiation of EB by a special apparatus has been applied to analyze the charging dynamics, which gives information on both resistance and capacitance.…”
Section: Introductionmentioning
confidence: 99%
“…Electron beam inspection (EBI) methodology, implemented through the use of VC to differentiate the failing site, is widely used in industry for in-line electrical defect monitoring [1][2][3]. It provides timely information on the factors for yield detractors so that proper steps can be taken to rectify the problems promptly.…”
Section: Introductionmentioning
confidence: 99%